Mathematics Learning in the Difusi Era: Strategies and Challenges in Madrasah Ibtidaiyah - Diana, Risma Chulashotud; Prapti Octavia Ningsih; Yuni Azura (PIONIR: JURNAL PENDIDIKAN, 2026)
This study aims to examine the effectiveness of the application of Project-Based Learning strategies combined with digital classroom media in learning basic mathematics for prospective elementary school teachers. The background of this research is based on students' low interest and understanding of mathematics, as well as the dominance of conventional learning approaches that are still teacher-centered. Through the Project-Based Learning approach, students are involved in making project-based learning media according to math materials such as KPK, FPB, whole numbers, fractions, and flat shapes. This process is also strengthened by the use of digital media for discussion, collaboration, and online task collection. The research used a quantitative descriptive approach with data collection techniques in the form of questionnaires distributed to 24 students. The results showed that 58.3% really understood the material taught, and 79.1% considered the learning strategy used to be effective. In conclusion, the digital classroom-based Project-Based Learning strategy is able to increase students' involvement, understanding, and motivation to learn mathematics. This approach also trains 21st century skills such as collaboration, creativity, and communication, and prepares students as competent teachers in the digital era. Keywords: Project-Based Learning, Digital Classroom, Mathematics Learning, Prospective Teacher Students, Learning Strategy